Solving Equations 7

Easy

Medium

Difficult

Q1) 4(5y -4) = 44
Q1) \(8z -6 = 6z + 4\)
Q1) \(2(y + 2) = 3y +7\)
Q2) 6(6y -10) = 12
Q2) \(9z -12 = 6z + 18\)
Q2) \(6(x + 3) = 10x -10\)
Q3) 5(3x + 2) = 70
Q3) \(10w -8 = 4w + 16\)
Q3) \(3(x -10) = 5x -10\)
Q4) 2(8y -3) = 74
Q4) \(10w -13 = 8w + 11\)
Q4) \(5(z -4) = 10z +5\)
Q5) 2(9z -6) = 24
Q5) \(5x -17 = 2x + 13\)
Q5) \(3(x + 9) = 6x -3\)
Q6) 8(8z -9) = 56
Q6) \(9w -16 = 6w + 17\)
Q6) \(3(x + 5) = 4x +7\)
Q7) 3(3y -3) = 45
Q7) \(4z + 7 = 2z + 13\)
Q7) \(4(x + 3) = 9x +2\)
Q8) 3(5w -4) = 48
Q8) \(10z -16 = 6z + 12\)
Q8) \(3(y -10) = 8y +5\)
Q9) 10(4z -10) = 20
Q9) \(7x -4 = 4x + 5\)
Q9) \(2(z + 10) = 3z +10\)
Q10) 4(3z -9) = 24
Q10) \(4z -20 = 2z + 14\)
Q10) \(2(y + 10) = 7y +5\)